The dangerous use of inhalants among teens: A case report - Ermelinda Levari; Martina Stefani; Roberta Ferrucci; Attilio Negri; Ornella Corazza (Elsevier, 2021)
The recreational use of inhalants among teenagers and other vulnerable individuals is a growing cause of concern for clinicians. Products, such as computer dusters and spray cleaners containing highly toxic compounds, are being used to obtain immediate euphoric effects with significant health risks. In this article we provide an overview of this new drug trend and present a case report of a 14-year-old girl, who was admitted at our Addiction Treatment Unit (Ser.D) in Trento (Italy) after inhalant use. The lack of literature in the field suggests the need for further investigations on such hazardous practices and more targeted prevention approaches aimed at informing adolescents, parents and clinicians working with them.